2000
DOI: 10.1046/j.1525-1470.2000.01701.x
|View full text |Cite
|
Sign up to set email alerts
|

Vulvar Disease in Children: A Clinical Audit of 130 Cases

Abstract: We evaluated 130 prepubertal girls presenting with a vulvar complaint to determine the spectrum and frequency of conditions seen in this age group. Of the patients, 41 (33%) had atopic or irritant dermatitis, 23 (18%) had lichen sclerosus, 21 (17%) had psoriasis, 15 (12%) had vulvar lesions, most often hemangiomas and nevi, and 13 (10%) had streptococcal vulvovaginitis. Diagnoses less frequently seen were staphylococcal folliculitis (four patients), labial fusion (three patients), genital warts (two patients),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
82
4
8

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(100 citation statements)
references
References 16 publications
6
82
4
8
Order By: Relevance
“…Our finding is in contrast to studies quoted in western literature where lichen sclerosus et atrophicus was the most most frequently observed vulvar dermatoses. 8,11,12 The reason for this variation could be due to the age group of patients in our study which mainly comprised of women of reproductive age group, while it has been mentioned in medical literature that LSA has two peak ages of presentation: prepubertal and post-menopausal. A study of 350 women with LSA by Thomas et al showed that the mean age of patients was 56 years.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Our finding is in contrast to studies quoted in western literature where lichen sclerosus et atrophicus was the most most frequently observed vulvar dermatoses. 8,11,12 The reason for this variation could be due to the age group of patients in our study which mainly comprised of women of reproductive age group, while it has been mentioned in medical literature that LSA has two peak ages of presentation: prepubertal and post-menopausal. A study of 350 women with LSA by Thomas et al showed that the mean age of patients was 56 years.…”
mentioning
confidence: 89%
“…8 Similarly Fischer et al conducted a prospective study of 141 patients with vulvar complaints and the most common vulvar dermatoses noted were lichen sclerosus (13%), vulvovaginal candidiasis (10%), vulvodynia (9%) and psoriasis (5%). 12 The approach to patients with vulvar disorders varies from country to country. However, multidisciplinary clinics seem to improve the understanding of vulvar diseases, to make correct diagnoses and to raise patients' quality of life.…”
mentioning
confidence: 99%
“…The need to search for nail pitting, scalp or postauricular erythema and scaling during paediatric clinical examination was also emphasized [13]. In a Clinical Audit of 130 cases of vulvar disease in children the authors reported that psoriasis is one of the most common dermatoses in prepubertal girls, but it may involve any age group including infants ("napkin psoriasis") [13][14]. Vulva itch and rashes are usually the symptoms presented to a paediatrician or general practitioner.…”
Section: Symptomsmentioning
confidence: 99%
“…Vulva itch and rashes are usually the symptoms presented to a paediatrician or general practitioner. The possibility of sexual abuse should not be omitted, especially when the child presents symptoms of a sexually transmitted disease or evidence of trauma is seen [14].…”
Section: Symptomsmentioning
confidence: 99%
“…Signs and symptoms include irritation and erythema of the vulva, vaginal discharge, soreness, itching, dysuria, and bleeding [4][5][6][7]. Vulvovaginitis is generally considered to be the commonest gynecological problem in prepubertal girls [1][2][3].…”
Section: Introductionmentioning
confidence: 99%